COMMUNICATIVE-FUNCTIONAL APPROACH WHEN TEACHING A SINGLE COMPOSITE SENTENCE - N.M. Sharmanova (Academy of Cognitive and Natural Sciences, 2008)
The article covers on the lingvistic and didactic's basis of communication and functional study of the mononuclear sentences of learning in modem lessons on Ukrainian language.